PENGARUH PENEMPATAN KERJA TERHADAP PRESTASI KERJA - BUDI ISWOYO (AKADEMIKA, 2020)
This study aims to determine and analyze the effect of job placement variables on employee job performance. The sample used in the study amounted to 50 respondents according to the population in the research object. This study uses a quantitative approach with data collection techniques using questionnaires, interviews, and literature study. The research results prove that the independent variable in this study is the Job Placement variable (X) which has a positive and significant effect on the Job Performance variable (Y).